Neumann's tumor in new born: A case requiring surgical intervention - Murali Nirupama; Ganesh Pai; Anand Pai; Reshma Pai (Wolters Kluwer Medknow Publications, 2014)
Congenital epulis (CE) also known as granular cell tumor of new born was first described by Neumann in the year 1871. Most frequent location includes maxillary alveolar ridge with a female preponderance up to 8 times more than males. These tumors are usually small and can be solitary or multiple, pedunculated or protuberant mucosa covered nodules presenting at birth. Multiple theories have been proposed for their origin. Though, it may cause panic at birth they are indolent and regress spontaneously. Rare cases require surgical intervention in the neonatal period when symptomatic, causing difficulties in respiration or deglutition. We describe a case of CE in a 2-day-old female neonate, who presented with pink protuberant mass in the anterior alveolar ridge of maxilla. The mass was symptomatic and surgery was indicated. The mass was excised and the benign nature was confirmed by histopathology.